John Sharpe papers - Sharpe, John.
Letter to Sharpe, bills, notes, petitions, and testimony pertaining to the exportation of sugar from British colonies in America to foreign ports.
British lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sugar trade -- Great Britain; Great Britain -- Colonies -- America; Great Britain -- Commerce -- History -- 18th century; Lawyers